Desain dan Implementasi Website Pengaduan Masyarakat Berbasis Rule-Based System pada Dinas Sosial Kabupaten Flores Timur - Yohanes Tenuper Hewen; Bernadete Deta; Martinus Irwanto Ishak (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Public complaint services at the East Flores Regency Social Service Office previously relied on direct visits and personal social media accounts, which limited integrated recording, identity verification, status monitoring, and initial responses. This study designs a web-based complaint website and application, implements a Rule-Based System, and evaluates functionality and user acceptance. The system was developed using the Waterfall model. IF-THEN rules validate data, classify complaints, assign responsible units, moderate language, and generate initial responses. The system provides service information, complaint submission, WhatsApp OTP, reference numbers, status tracking, document upload, an administrator panel, a response knowledge base, and Fonnte notifications. Black Box Testing covered 45 scenarios, of which 44 passed, resulting in a 97.78% functional success rate. Beta Testing with 50 respondents and 20 statements produced a score of 4,161 out of 5,000 or 83.22%, classified as Very Good. All 20 items were valid, with item-total correlations from 0.646 to 0.830, while Cronbach's Alpha reached 0.968. The overall usability score was 83.01%, including effectiveness at 82.72%, efficiency at 83.12%, and user satisfaction at 83.20%. The system met functional requirements and received very good user acceptance in the test environment. Public HTTPS deployment, webhook, load, security, and recovery testing remain necessary before broad implementation.